Grazing wheat did not reduce beef cow pregnancy rates - Johnson, Sandra K.; Harmoney, Keith R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Beef producers can lower feed costs by extending the grazing period and reducing the need for harvested forages. Complementary forage systems extend the native range grazing season; wheat pasture is common in the southern portion of the High Plains. Anecdotal reports have been made concerning lowered fertility in beef cows bred on lush forage such as wheat pasture; however, ruling out other possible causes of low fertility is difficult. In lactating dairy cows, fertility is lower during consumption of high-protein diets that result in high blood urea nitrogen content. Lower uterine pH that in turn affects embryo survival is thought to be the general mechanism responsible for lower fertility. Little information is available on the fertility of beef cows consuming high-protein diets. Therefore, the objective of this study was to compare pregnancy rates of springcalving cows consuming either wheat pasture or native range before and during the early breeding season.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Wheat; Pregnancy rates; Fertility